PCB congener data of gas-phase, dissolved water, air-water fluxes in southern Lake Michigan, 2010 - Aaron C Boesen; Andres Martinez; Keri C Hornbuckle (PANGAEA, 2019)
Airborne and dissolved water PCB congener specific concentrations from southern Lake Michigan 2010. The data were used to estimated instantaneous air-water PCB fluxes.
Supplement to: Boesen, AC et al. (2019): Air-water PCB fluxes from southwestern Lake Michigan revisited. Environmental Science and Pollution Research, https://doi.org/10.1007/s11356-019-05159-1